Positive pole piece as well as preparation method and application thereof
By setting layered oxide materials and polyanionic positive electrode materials in the positive electrode sheet of the sodium ion battery and adjusting their proportions, the problems of taking into account both the energy density and cycle life of the positive electrode material of the sodium ion battery are solved, and high capacity and excellent Thermal stability and cyclic stability.
Patent Information
- Application Number
- CN202411353989.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2024-12-31
AI Technical Summary
The positive electrode materials of existing sodium ion batteries are difficult to take into account between energy density and cycle life. The layered oxide materials have high energy density but poor structural stability, and polyanionic materials have stable structure but low energy density.
By setting the layered oxide material as the first main material layer and the polyanionic positive electrode material as the second main material layer in the positive electrode sheet, and adjusting its mass ratio and conductive agent ratio, the capacity and cycling performance of the battery are ensured.
The high capacity, excellent thermal stability and cyclic stability of the positive electrode sheet are achieved, and are suitable for sodium ion batteries, overcoming the contradiction between material structural stability and energy density in the prior art.
Smart Images

Figure BDA0005063833170000171 
Figure BDA0005063833170000181
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries and relates to a positive electrode sheet and a preparation method and application thereof. Background Art
[0002] Due to the limited lithium in the earth's crust, the cost of lithium-ion batteries is increased. Sodium and lithium belong to the same main group elements. The working principle of sodium-ion batteries is similar to that of lithium-ion batteries. In addition, the content of sodium in the earth's crust is higher than that of lithium, which makes sodium-ion batteries have the advantages of low cost and high safety factor. Therefore, sodium-ion batteries can replace lithium-ion batteries.
[0003] The main factor affecting the performance of sodium-ion batteries is the sodium-ion cathode material. Common sodium-ion cathode materials are layered oxide materials and polyanion cathode materials. Layered oxide materials have higher energy density and have certain advantages in sodium-ion cathodes, but due to poor structural stability, the cycle life cannot be guaranteed. Polyanion cathode materials have better ion transport and structural stability, and have certain advantages in sodium-ion cathodes, but their energy density is low and they cannot provide excellent electrochemical performance for power vehicles.
[0004] Based on the above research, it is necessary to provide a positive electrode plate that can take into account both the energy density and cycle performance of sodium ion batteries. Summary of the invention
[0005] The object of the present invention is to provide a positive electrode plate and a preparation method and application thereof. The positive electrode plate can not only ensure the capacity of the positive electrode plate but also have excellent thermal stability and cycle stability by adjusting the type and mass ratio of the positive electrode material in the first main material layer and the second main material layer.
[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a positive electrode plate, the positive electrode plate comprising a current collector and a positive electrode main material layer disposed on at least one side of the current collector, the positive electrode main material layer comprising a first main material layer on the surface of the current collector, and a second main material layer disposed on a side of the first main material layer away from the current collector;
[0008] The first main material layer includes a layered oxide material, and the second main material layer includes a polyanion positive electrode material;
[0009] The mass ratio of the layered oxide material to the polyanion positive electrode material is (1-3):(3.1-5).
[0010] Preferably, the first main material layer also includes a first conductive agent, the second main material layer also includes a second conductive agent, the mass ratio of the first conductive agent to the second conductive agent is y1, the mass ratio of the layered oxide material to the polyanion positive electrode material is x, and y1 and x satisfy a binary linear relationship.
[0011] Preferably, y1 and x satisfy the following relationship: y1 = a1x 2 +b1x+c1, wherein a1 is 6.55-6.65, b1 is 6.45-6.55, and c1 is -7.0 to -2.5, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0012] Preferably, the first main material layer also includes a first conductive agent, and the second main material layer also includes a second conductive agent. The sum of the mass fractions of the first conductive agent and the second conductive agent / (the sum of the mass fractions of the layered oxide material and the polyanion positive electrode material)×100 is y2, the thickness ratio of the first main material layer and the second main material layer is z, and y2 and z satisfy a binary linear relationship.
[0013] Preferably, y2 and z satisfy the following relationship: y2=a2z 2 -b2z+c2, where a2 is 2.2-2.4, b2 is 2.5-3, and c2 is 5-6.
[0014] Preferably, the thickness ratio of the first main material layer to the second main material layer is (3-5):(6-8).
[0015] Preferably, the first conductive agent includes any one of graphite, multi-walled carbon nanotubes, graphene, SP (conductive carbon black) or acetylene black, or a combination of at least two thereof, preferably multi-walled carbon nanotubes.
[0016] Preferably, the second conductive agent includes any one of graphite, multi-walled carbon nanotubes, graphene, SP or acetylene black or a combination of at least two thereof, preferably any one of graphite, graphene, SP or acetylene black or a combination of at least two thereof.
[0017] Preferably, the first main material layer further includes a first adhesive.
[0018] Preferably, in the first main material layer, the mass ratio of the layered oxide material, the first conductive agent and the first binder is (25-40):(0.8-1.6):(0.3-1.2), for example, it can be 25:0.8:1.2, 30:1:0.5, 35:1.6:1.2 or 40:1.6:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0019] Preferably, the second main material layer further includes a second adhesive.
[0020] Preferably, in the second main material layer, the mass ratio of the polyanion positive electrode material, the second conductive agent and the second binder is (59-78):(3-4):(1.2-1.6), for example, it can be 59:3:1.2, 65:3.5:1.4 or 78:4:1.6, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0021] Preferably, the layered oxide material includes any one of sodium nickel cobalt manganate, sodium metaferrite or sodium nickel cobalt aluminum oxide, or a combination of at least two thereof.
[0022] Preferably, the polyanion positive electrode material includes sodium vanadium phosphate and / or sodium vanadium fluorophosphate.
[0023] In a second aspect, the present invention provides a method for preparing the positive electrode sheet, the method comprising the following steps:
[0024] (1) coating a first main material layer slurry on at least one side surface of a current collector, and after drying, obtaining a first main material layer on at least one side surface of the current collector;
[0025] (2) coating the second main material layer slurry on the surface of the first main material layer in step (1), and after drying, obtaining a positive electrode main material layer on at least one side of the current collector to obtain the positive electrode sheet;
[0026] The first main material layer slurry includes a layered oxide material, and the second main material layer slurry includes a polyanion positive electrode material;
[0027] The mass ratio of the layered oxide material to the polyanion positive electrode material is (1-3):(3.1-5).
[0028] In a third aspect, the present invention provides a battery, comprising the positive electrode sheet as described in the first aspect, or the positive electrode sheet prepared by the preparation method as described in the second aspect.
[0029] In a fourth aspect, the present invention provides an electrical device, wherein the electrical device comprises the battery as described in the third aspect.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] (1) The present invention uses layered oxides in the first main material layer to ensure the capacity of the battery core, and uses polyanion positive electrode materials in the second main material layer to make the positive electrode have good thermal stability and cycle stability;
[0032] (2) The present invention improves the capacity and cycle performance of the sodium ion battery by adjusting the ratio of the main materials in the first main material layer and the second main material layer;
[0033] (3) In order to achieve the balance between lithium ion embedding and embedding in the first main material layer and the second main material layer, the conductive agent of the first main material layer uses multi-walled carbon nanotubes to improve the transfer rate, and the conductive agent of the second main material layer uses non-multi-walled carbon nanotubes;
[0034] (4) The present invention constructs a functional relationship between the positive electrode main material and the conductive agent to obtain the optimal formula range, and achieves the maximum gram capacity and the improvement of the optimal cycle performance by adjusting different formulas and different thicknesses;
[0035] (5) The preparation process of the present invention is simple and can be easily industrialized. DETAILED DESCRIPTION
[0036] In order to solve the problem that layered oxide materials have high energy density but poor structural stability and cannot guarantee cycle life, while polyanion compounds have good ion transport and structural stability but low energy density, the present invention provides a positive electrode plate with both high capacity and excellent cycle performance.
[0037] In a specific embodiment, a positive electrode plate is provided, the positive electrode plate comprising a current collector and a positive electrode main material layer disposed on at least one side of the current collector, the positive electrode main material layer comprising a first main material layer on the surface of the current collector, and a second main material layer disposed on a side of the first main material layer away from the current collector;
[0038] The first main material layer includes a layered oxide material, and the second main material layer includes a polyanion positive electrode material;
[0039] The mass ratio of the layered oxide material to the polyanion positive electrode material is (1-3):(3.1-5), for example, it can be 1:3.1, 2:3.5, 2:4, 2:5, 3:3.1 or 3:5, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0040] The present invention uses the inner layer close to the current collector as the first main material layer, and adopts layered oxide material as the main material to ensure the capacity of the positive electrode plate, and uses the outer layer away from the current collector as the second main material layer, and adopts polyanion positive electrode material as the main material to ensure that the positive electrode plate has good thermal stability and cycle stability; at the same time, due to the different positions of the first main material layer and the second main material layer, the transmission rates are different, and the capacity and cycle performance of the battery are comprehensively improved by adjusting the ratio of the main materials in the first main material layer and the second main material layer. If the proportion of the layered oxide material is too small, the gram capacity is not obvious, and a large proportion affects the cycle performance. If the proportion of the polyanion positive electrode material in the second main material layer is too small, the cycle performance is not improved much, and a large proportion leads to insufficient capacity improvement.
[0041] Preferably, the first main material layer also includes a first conductive agent, and the second main material layer also includes a second conductive agent. The mass ratio of the first conductive agent to the second conductive agent is y1, and the mass ratio of the layered oxide material (first positive electrode main material) to the polyanion positive electrode material (second positive electrode main material) is x. y1 and x satisfy a binary linear relationship.
[0042] Preferably, y1 and x satisfy the following relationship: y1 = a1x 2 +b1x+c1, wherein a1 is 6.55-6.65, for example, 6.55, 6.6 or 6.65, b1 is 6.45-6.55, for example, 6.45, 6.5 or 6.55, c1 is -7.0 to -2.5, for example, -7.0, -6.0, -5.0, -4.0, -3.0 or -2.5, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0043] In the first main material layer and the second main material layer of the present invention, the proportion of the conductive agent is in a functional relationship with the proportion of the main material. As the mass ratio x of the first positive electrode main material to the second positive electrode main material increases, the relative content of the first positive electrode main material gradually increases, and the relative content of the second positive electrode main material gradually decreases. When the mass ratio x of the first positive electrode main material to the second positive electrode main material is small, the content of the first positive electrode main material in the first main material layer is much smaller than the content of the second positive electrode main material in the second main material layer. In order to ensure the normal transmission of lithium ions, the content of the first conductive agent increases with the increase of the content of the first positive electrode main material in the first main material layer, and the content of the second conductive agent decreases with the decrease of the content of the second positive electrode main material in the second main material layer. There is an interface resistance between the first main material layer and the second main material layer. When the content of the first main material layer is small, the interface resistance has little effect on the transmission of lithium ions. As the content of the first main material layer increases, its interface resistance gradually increases. It is necessary to add more first conductive agent to the first main material layer to overcome the influence of the interface resistance and ensure the normal transmission of lithium ions. Therefore, the mass ratio y1 of the first conductive agent to the second conductive agent increases with the increase of x, and the increase increases with the increase of x. Therefore, it is further verified that y1 and the x satisfy the quadratic function relationship.
[0044] Preferably, the first main material layer also includes a first conductive agent, and the second main material layer also includes a second conductive agent. The sum of the mass fractions of the first conductive agent and the second conductive agent / (the sum of the mass fractions of the layered oxide material and the polyanion positive electrode material)×100 is y2, the thickness ratio of the first main material layer and the second main material layer is z, and y2 and z satisfy a binary linear relationship.
[0045] Preferably, y2 and z satisfy the following relationship: y2=a2z 2 -b2z+c2, wherein a2 is 2.2-2.4, such as 2.2, 2.3 or 2.4, b2 is 2.5-3, such as 2.5, 2.8 or 3, and c2 is 5-6, such as 5, 5.5 or 6, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0046] In the first main material layer and the second main material layer of the present invention, the sum of the mass fractions of the first conductive agent and the second conductive agent is in a functional relationship with the thickness ratio. As the thickness ratio z increases, the relative thickness of the first main material layer gradually increases, and the relative thickness of the second main material layer gradually decreases. When the thickness ratio z is small, the thickness of the second main material layer is much greater than the thickness of the first main material layer. Since the distance between the interface between the first main material layer and the second main material layer and the current collector is relatively small at this time, the interface resistance has little effect on the transmission of lithium ions. At this time, the thickness of the second main material layer is the key factor affecting the transmission of lithium ions. As the relative thickness of the second main material layer gradually decreases, the transmission of lithium ions is relatively easy, and the amount of conductive agent required for the first main material layer and the second main material layer gradually decreases, that is, the sum of the mass fractions y2 of the first conductive agent and the second conductive agent gradually decreases. When the thickness ratio z is large, the thickness of the first main material layer is close to the thickness of the second main material layer, that is, the first main material layer is thicker, the distance between the interface between the first main material layer and the second main material layer and the current collector is relatively large, and the interface resistance is large. At this time, the thickness of the first main material layer is a key factor affecting the transmission of lithium ions. As the relative thickness of the first main material layer gradually increases, the transmission of lithium ions is relatively difficult, and the amount of conductive agent required for the first main material layer and the second main material layer gradually increases, that is, y2 gradually increases. Therefore, it is further verified that y2 and the z satisfy the quadratic function relationship.
[0047] Preferably, the thickness ratio of the first main material layer and the second main material layer is (3-5):(6-8), for example, it can be 3:8, 4:5 or 5:6, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0048] The thickness ratio of the first main material layer and the second main material layer of the present invention needs to be controlled. If the first main material layer is too thin, the advantage of the first main material layer in increasing capacity cannot be brought into play. If the second main material layer is too thin, the circulation advantage cannot be brought into play. Based on this, when the thickness of the first main material layer is relatively thin, it is beneficial to the circulation performance. When the thickness of the first main material layer is relatively thick, it is beneficial to the capacity. Therefore, if the first main material layer is too thick, the internal heat diffusion is poor, resulting in a decrease in the circulation capacity. At the same time, if it is too thick, the internal resistance of the battery cell increases, which is not conducive to the electrical performance.
[0049] Preferably, the first conductive agent includes any one of graphite, multi-walled carbon nanotubes, graphene, SP or acetylene black, or a combination of at least two thereof, preferably multi-walled carbon nanotubes.
[0050] Preferably, the second conductive agent includes any one of graphite, multi-walled carbon nanotubes, graphene, SP or acetylene black or a combination of at least two thereof, preferably any one of graphite, graphene, SP or acetylene black or a combination of at least two thereof.
[0051] Since the embedding and unembedding of the first main material layer is slower than that of the second main material layer, the conductive agent in the first main material layer uses multi-walled carbon nanotubes to increase the transfer rate, and the conductive agent in the second main material layer uses non-multi-walled carbon nanotubes to achieve a balance between the embedding and unembedding of the first main material layer and the second main material layer, thereby ensuring the normal performance of the battery capacity.
[0052] The non-multi-walled carbon nanotubes in the present invention refer to conductive agents other than multi-walled carbon nanotubes, such as graphite, graphene, SP or acetylene black.
[0053] Preferably, the first main material layer further includes a first adhesive.
[0054] Preferably, in the first main material layer, the mass ratio of the layered oxide material, the first conductive agent and the first binder is (25-40):(0.8-1.6):(0.3-1.2), for example, it can be 25:0.8:1.2, 30:1:0.5, 35:1.6:1.2 or 40:1.6:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0055] The mass ratio of the layered oxide material, the first conductive agent and the first binder in the first main material layer of the present invention is within a specific range, which can ensure that the layered oxide material, the first conductive agent and the first binder can function properly.
[0056] Preferably, the second main material layer further includes a second adhesive.
[0057] Preferably, in the second main material layer, the mass ratio of the polyanion positive electrode material, the second conductive agent and the second binder is (59-78):(3-4):(1.2-1.6), for example, it can be 59:3:1.2, 65:3.5:1.4 or 78:4:1.6, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0058] The mass ratio of the polyanion positive electrode material, the second conductive agent and the second binder in the second main material layer of the present invention is within a specific range, which can ensure that the functions of the polyanion positive electrode material, the second conductive agent and the second binder are exerted.
[0059] Preferably, the layered oxide material includes any one of sodium nickel cobalt manganate, sodium metaferrite or sodium nickel cobalt aluminum oxide, or a combination of at least two thereof.
[0060] Preferably, the polyanion positive electrode material includes sodium vanadium phosphate and / or sodium vanadium phosphate.
[0061] In a specific embodiment, a method for preparing the positive electrode sheet is provided, and the preparation method comprises the following steps:
[0062] (1) coating a first main material layer slurry on at least one side surface of a current collector, and after drying, obtaining a first main material layer on at least one side surface of the current collector;
[0063] (2) coating the second main material layer slurry on the surface of the first main material layer in step (1), and after drying, obtaining a positive electrode main material layer on at least one side of the current collector to obtain the positive electrode sheet;
[0064] The first main material layer slurry includes a layered oxide material, and the second main material layer slurry includes a polyanion positive electrode material;
[0065] The mass ratio of the layered oxide material to the polyanion positive electrode material is (1-3):(3.1-5), for example, it can be 1:3.1, 2:3.5, 2:4, 2:5, 3:3.1 or 3:5, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0066] Preferably, in the first main material layer slurry, the mass ratio of the layered oxide material, the first conductive agent and the first binder is (25-40):(0.8-1.6):(0.3-1.2), for example, it can be 25:0.8:1.2, 30:1:0.5, 35:1.6:1.2 or 40:1.6:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0067] Preferably, in the first main material layer slurry, the mass fraction of layered oxide material is 25-40 parts, for example, it can be 25 parts, 30 parts, 35 parts or 40 parts, the mass fraction of the first conductive agent is 0.8-1.6 parts, for example, it can be 0.8 parts, 1.2 parts or 1.6 parts, the mass fraction of the first binder is 0.3-1.2 parts, for example, it can be 0.3 parts, 0.8 parts or 1.2 parts, the mass fraction of the solvent is 20-30 parts, for example, it can be 20 parts, 25 parts or 30 parts, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0068] Preferably, in the second main material layer slurry, the mass ratio of the polyanion positive electrode material, the second conductive agent and the second binder is (59-78):(3-4):(1.2-1.6), for example, it can be 59:3:1.2, 65:3.5:1.4 or 78:4:1.6, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0069] Preferably, in the second main material layer slurry, the mass fraction of the polyanion positive electrode material is 59-78 parts, for example, it can be 59 parts, 65 parts, 70 parts or 78 parts, the mass fraction of the second conductive agent is 3-4 parts, for example, it can be 3 parts, 3.5 parts or 78 parts, the mass fraction of the second binder is 1.2-1.6 parts, for example, it can be 1.2 parts, 1.4 parts or 1.6 parts, the mass fraction of the solvent is 40-50 parts, for example, it can be 40 parts, 45 parts or 50 parts, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0070] In a specific embodiment, a battery is provided, wherein the battery comprises the positive electrode plate as described above, or the positive electrode plate prepared by the preparation method as described above.
[0071] In a specific embodiment, an electric device is provided, and the electric device includes the battery.
[0072] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0073] Example 1
[0074] This embodiment provides a positive electrode plate, the positive electrode plate comprising an aluminum foil and a positive electrode main material layer disposed on both sides of the aluminum foil, the positive electrode main material layer comprising a first main material layer on the surface of the aluminum foil, and a second main material layer disposed on a side of the first main material layer away from the aluminum foil;
[0075] The first main material layer includes a layered oxide material, multi-walled carbon nanotubes and PVDF in a mass ratio of 25:0.8:0.3, and the layered oxide material is sodium nickel cobalt manganate;
[0076] The second main material layer includes a polyanion positive electrode material, SP and PVDF in a mass ratio of 78:4:1.6, and the polyanion positive electrode material is sodium vanadium phosphate;
[0077] The mass ratio of the layered oxide material to the polyanion positive electrode material is 1:3.12, the mass fraction of the multi-walled carbon nanotubes is 0.8 parts, the mass fraction of SP (conductive carbon black) is 4 parts, the mass ratio of the multi-walled carbon nanotubes to SP is y1=0.2, the mass ratio of the layered oxide material to the polyanion positive electrode material is x=0.32, and y1 and x satisfy the following relationship: y1=6.55x 2 +6.55x-2.56;
[0078] The thickness ratio of the first main material layer to the second main material layer is 3:6.9, the sum of the mass fractions of the multi-walled carbon nanotubes and SP / (the sum of the mass fractions of the layered oxide material and the polyanion positive electrode material)×100 is y2=4.66, the thickness ratio of the first main material layer to the second main material layer is z=0.43, and y2 and z satisfy the following relationship: y2=2.34z 2 -2.88z+5.47;
[0079] The method for preparing the positive electrode sheet comprises the following steps:
[0080] (1) 25 parts of sodium nickel cobalt manganate, 0.8 parts of multi-walled carbon nanotubes and 0.3 parts of PVDF (polyvinylidene fluoride) were added with 20 parts of NMP (N-methylpyrrolidone) and stirred to form a first main material layer slurry. The first main material layer slurry was coated on both sides of the aluminum foil and dried to obtain a first main material layer with a thickness of 90 mm;
[0081] (2) 78 parts of sodium vanadium phosphate, 4 parts of SP and 1.6 parts of PVDF were added with 50 parts of NMP, stirred into a second main material layer slurry, coated on the surface of the first main material layer in step (1), and dried to obtain a second main material layer with a thickness of 207 mm, thereby obtaining the positive electrode sheet.
[0082] Example 2
[0083] This embodiment provides a positive electrode plate, the positive electrode plate comprising an aluminum foil and a positive electrode main material layer disposed on both sides of the aluminum foil, the positive electrode main material layer comprising a first main material layer on the surface of the aluminum foil, and a second main material layer disposed on a side of the first main material layer away from the aluminum foil;
[0084] The first main material layer includes a layered oxide material, multi-walled carbon nanotubes and PVDF in a mass ratio of 30:1.2:0.8, and the layered oxide material is sodium nickel cobalt manganate;
[0085] The second main material layer includes a polyanion positive electrode material, SP and PVDF in a mass ratio of 72:3.5:1.4, and the polyanion positive electrode material is sodium vanadium phosphate;
[0086] The mass ratio of the layered oxide material to the polyanion positive electrode material is 2:4.8, the mass fraction of the multi-walled carbon nanotubes is 1.2 parts, the mass fraction of SP is 3.5 parts, the mass ratio of the multi-walled carbon nanotubes to SP is y1=0.34, the mass ratio of the layered oxide material to the polyanion positive electrode material is x=0.42, and y1 and x satisfy the following relationship: y1=6.61x 2 +6.51x-3.56;
[0087] The thickness ratio of the first main material layer to the second main material layer is 4:8, the sum of the mass fractions of the multi-walled carbon nanotubes and SP / (the sum of the mass fractions of the layered oxide material and the polyanion positive electrode material)×100 is y2=4.61, the thickness ratio of the first main material layer to the second main material layer is z=0.5, and y2 and z satisfy the following relationship: y2=2.2z 2 -2.88z+5.5;
[0088] The method for preparing the positive electrode sheet comprises the following steps:
[0089] (1) 30 parts of sodium nickel cobalt manganate, 1.2 parts of multi-walled carbon nanotubes and 0.8 parts of PVDF were added with 25 parts of NMP and stirred to form a first main material layer slurry. The first main material layer slurry was coated on both sides of the aluminum foil and dried to obtain a first main material layer with a thickness of 120 mm;
[0090] (2) 72 parts of sodium vanadium phosphate, 3.5 parts of SP and 1.4 parts of PVDF were added with 45 parts of NMP, stirred into a second main material layer slurry, coated on the surface of the first main material layer in step (1), and dried to obtain a second main material layer with a thickness of 241 mm, thereby obtaining the positive electrode sheet.
[0091] Example 3
[0092] This embodiment provides a positive electrode plate, the positive electrode plate comprising an aluminum foil and a positive electrode main material layer disposed on both sides of the aluminum foil, the positive electrode main material layer comprising a first main material layer on the surface of the aluminum foil, and a second main material layer disposed on a side of the first main material layer away from the aluminum foil;
[0093] The first main material layer includes a layered oxide material, multi-walled carbon nanotubes and PVDF in a mass ratio of 40:1.6:1.2, and the layered oxide material is sodium nickel cobalt manganate;
[0094] The second main material layer includes a polyanion positive electrode material, SP and PVDF in a mass ratio of 59:3:1.2, and the polyanion positive electrode material is sodium vanadium phosphate;
[0095] The mass ratio of the layered oxide material to the polyanion positive electrode material is 2.5:3.68, the mass fraction of the multi-walled carbon nanotubes is 1.6 parts, the mass fraction of SP is 3 parts, the mass ratio of the multi-walled carbon nanotubes to SP is y1=0.53, the mass ratio of the layered oxide material to the polyanion positive electrode material is x=0.68, and y1 and x satisfy the following relationship: y1=6.6x 2 +6.5x-6.94;
[0096] The thickness ratio of the first main material layer to the second main material layer is 4:6.58, the sum of the mass fractions of the multi-walled carbon nanotubes and SP / (the sum of the mass fractions of the layered oxide material and the polyanion positive electrode material)×100 is y2=4.65, the thickness ratio of the first main material layer to the second main material layer is z=0.61, and y2 and z satisfy the following relationship: y2=2.4z 2 -3z+5.59;
[0097] The method for preparing the positive electrode sheet comprises the following steps:
[0098] (1) 40 parts of sodium nickel cobalt manganate, 1.6 parts of multi-walled carbon nanotubes and 1.2 parts of PVDF were added with 30 parts of NMP and stirred to form a first main material layer slurry. The first main material layer slurry was coated on both sides of the aluminum foil and dried to obtain a first main material layer with a thickness of 200 mm;
[0099] (2) 59 parts of sodium vanadium phosphate, 3 parts of SP and 1.2 parts of PVDF were added with 40 parts of NMP, stirred into a second main material layer slurry, coated on the surface of the first main material layer in step (1), and dried to obtain a second main material layer with a thickness of 329 mm, thereby obtaining the positive electrode sheet.
[0100] Example 4
[0101] This embodiment provides a positive electrode plate, the positive electrode plate comprising an aluminum foil and a positive electrode main material layer disposed on both sides of the aluminum foil, the positive electrode main material layer comprising a first main material layer on the surface of the aluminum foil, and a second main material layer disposed on a side of the first main material layer away from the aluminum foil;
[0102] The first main material layer includes a layered oxide material, multi-walled carbon nanotubes and PVDF in a mass ratio of 40:1.6:1.2, and the layered oxide material is sodium nickel cobalt manganate;
[0103] The second main material layer includes a polyanion positive electrode material, SP and PVDF in a mass ratio of 59:3:1.2, and the polyanion positive electrode material is sodium vanadium phosphate;
[0104] The mass ratio of the layered oxide material to the polyanion positive electrode material is 2.5:3.68, the mass fraction of the multi-walled carbon nanotubes is 1.6 parts, the mass fraction of SP is 3 parts, the mass ratio of the multi-walled carbon nanotubes to SP is y1=0.53, the mass ratio of the layered oxide material to the polyanion positive electrode material is x=0.68, and y1 and x satisfy the following relationship: y1=6.6x 2 +6.5x-6.94;
[0105] The thickness ratio of the first main material layer to the second main material layer is 3:6.9, the sum of the mass fractions of the multi-walled carbon nanotubes and SP / (the sum of the mass fractions of the layered oxide material and the polyanion positive electrode material)×100 is y2=4.65, the thickness ratio of the first main material layer to the second main material layer is z=0.43, and y2 and z satisfy the following relationship: y2=2.2z 2 -2.88z+5.48, among which;
[0106] The method for preparing the positive electrode sheet comprises the following steps:
[0107] (1) 40 parts of sodium nickel cobalt manganate, 1.6 parts of multi-walled carbon nanotubes and 1.2 parts of PVDF were added with 30 parts of NMP and stirred to form a first main material layer slurry. The first main material layer slurry was coated on both sides of the aluminum foil and dried to obtain a first main material layer with a thickness of 90 mm;
[0108] (2) 59 parts of sodium vanadium phosphate, 3 parts of SP and 1.2 parts of PVDF were added with 40 parts of NMP, stirred into a second main material layer slurry, coated on the surface of the first main material layer in step (1), and dried to obtain a second main material layer with a thickness of 207 mm, thereby obtaining the positive electrode sheet.
[0109] Example 5
[0110] This embodiment provides a positive electrode plate, which is the same as that of Embodiment 4 except that the multi-walled carbon nanotubes are replaced with SP.
[0111] Example 6
[0112] The present embodiment provides a positive electrode plate, which is the same as that of Embodiment 4 except that the thickness ratio of the first main material layer and the second main material layer is 1:1, the thickness of the first main material layer is 207 mm, the thickness of the second main material layer is 207 mm, and the relationship between y2 and z is adaptively changed.
[0113] Example 7
[0114] The present embodiment provides a positive electrode plate, which is the same as that of Embodiment 4 except that the thickness ratio of the first main material layer and the second main material layer is 2:8, the thickness of the first main material layer is 90 mm, the thickness of the second main material layer is 360 mm, and the relationship between y2 and z is adaptively changed.
[0115] Comparative Example 1
[0116] This comparative example provides a positive electrode plate, the positive electrode plate comprising an aluminum foil and a positive electrode main material layer disposed on both sides of the aluminum foil, the main material layer comprising a layered oxide material, multi-walled carbon nanotubes and PVDF in a mass ratio of 95:3:2, the layered oxide material is sodium nickel cobalt manganate, and the thickness of the main material layer is 270 mm;
[0117] The method for preparing the positive electrode sheet comprises the following steps:
[0118] 95 parts of sodium nickel cobalt manganate, 3 parts of multi-walled carbon nanotubes and 2 parts of PVDF were added with 55 parts of NMP, stirred into a main material layer slurry, coated on both sides of the aluminum foil, and dried to obtain a main material layer with a thickness of 270 mm, thereby obtaining the positive electrode sheet.
[0119] Comparative Example 2
[0120] This comparative example provides a positive electrode sheet, the positive electrode sheet comprising an aluminum foil and a positive electrode main material layer disposed on both sides of the aluminum foil, the main material layer comprising a polyanion positive electrode material, SP and PVDF in a mass ratio of 95:3:2, the polyanion positive electrode material is sodium vanadium phosphate, and the thickness of the main material layer is 270 mm;
[0121] The method for preparing the positive electrode sheet comprises the following steps:
[0122] 95 parts of sodium vanadium phosphate, 3 parts of SP and 2 parts of PVDF were added with 55 parts of NMP, stirred into a main material layer slurry, coated on both sides of the aluminum foil, and dried to obtain a main material layer with a thickness of 270 mm, thereby obtaining the positive electrode sheet.
[0123] Comparative Example 3
[0124] This comparative example provides a positive electrode sheet, in which the mass ratio of the layered oxide material to the polyanion positive electrode material is 1:1, and y1 and x do not satisfy the following relationship: y1=a1x 2 +b1x+c1, wherein a1 is 6.55-6.65, b1 is 6.45-6.55, c1 is -7 to -2.5, and the rest are the same as those in Example 4;
[0125] The preparation method of the positive electrode plate is the same as that of Example 4 except that the sodium vanadium phosphate is also 40 parts.
[0126] Comparative Example 4
[0127] This comparative example provides a positive electrode sheet, in which the mass ratio of the layered oxide material to the polyanion positive electrode material is 1:5.5, and y1 and x do not satisfy the following relationship: y1=a1x 2+b1x+c1, wherein a1 is 6.55-6.65, b1 is 6.45-6.55, c1 is -7 to -2.5, and the rest are the same as those in Example 4;
[0128] The preparation method of the positive electrode plate is the same as that of Example 4 except that the sodium nickel cobalt manganese oxide is 20 parts and the sodium vanadium phosphate is 110 parts.
[0129] The positive electrode sheets, separators and negative electrode sheets obtained in the above embodiments and comparative examples are wound into a core, wherein the separator completely covers the positive electrode sheet and the negative electrode sheet, and then the core is placed in a metal shell or wrapped with an aluminum-plastic film and injected with an electrolyte, and finally a sodium ion battery is made through processes such as standing, forming, and capacity separation; wherein the preparation of the negative electrode sheet includes: mixing hard carbon, SP, and PVDF with an appropriate amount of NMP in a ratio of 93:4:3 to prepare a negative electrode slurry, coating it on an aluminum foil, drying it with air at 100°C, and cold pressing and cutting it into negative electrode sheets.
[0130] Cycle test: At 25°C, the prepared battery was charged to 4.2V at 1C constant current and constant voltage, with a cut-off condition of 0.05C; after standing for 60 minutes, it was discharged to 2.0V at 1C, and the above process was continued until the capacity decayed to 80% of the initial test capacity, and the number of cycles was recorded.
[0131] Battery discharge capacity: Take the battery's first cycle discharge capacity as the battery capacity.
[0132] The test results are shown in Table 1:
[0133] Table 1
[0134]
[0135]
[0136] From Table 1 we can see that:
[0137] It can be seen from Example 4 and Comparative Examples 1-4 that the present invention designs main material layers on both sides, and the active layer of the first main material layer adopts a layered oxide material, and the active layer of the second main material layer adopts a polyanion positive electrode material, and there is a specific mass ratio between the layered oxide material and the polyanion positive electrode material, which can simultaneously ensure the battery capacity and cycle performance; It can be seen from Example 4 and Example 5 that since the embedding and embedding of the first main material layer are slower than those of the second main material layer, the present invention preferably adopts multi-walled carbon nanotubes in the first main material layer and non-multi-walled carbon nanotubes in the second main material layer to improve the battery capacity; It can be seen from Example 4 and Examples 6-7 that the thickness ratio of the first main material layer and the second main material layer of the present invention will affect the role of the two layers. If the first main material layer is too thin and the second main material layer is thicker than the first main material layer, the advantage of the first main material layer in increasing the capacity cannot be brought into play. If the first main material layer is thicker than the second main material layer, the second main material layer is too thin and the cycle advantage cannot be brought into play, thereby affecting the capacity and cycle performance of the battery.
[0138] In summary, the present invention provides a positive electrode plate and a preparation method and application thereof. The positive electrode plate is achieved by adjusting the type and mass ratio of the positive electrode materials in the first main material layer and the second main material layer, which can not only ensure the capacity of the positive electrode plate, but also enable the positive electrode plate to have excellent thermal stability and cycle stability.
[0139] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. A positive electrode sheet, characterized in that: The positive electrode sheet includes a current collector and a positive electrode main material layer disposed on at least one side of the current collector, wherein the positive electrode main material layer includes a first main material layer on the surface of the current collector, and a second main material layer disposed on a side of the first main material layer away from the current collector; The first main material layer includes a layered oxide material, and the second main material layer includes a polyanion positive electrode material; The mass ratio of the layered oxide material to the polyanion positive electrode material is (1-3):(3.1-5).
2. The positive electrode sheet according to claim 1, characterized in that: The first main material layer further includes a first conductive agent, the second main material layer further includes a second conductive agent, the mass ratio of the first conductive agent to the second conductive agent is y1, the mass ratio of the layered oxide material to the polyanion positive electrode material is x, and y1 and x satisfy a binary linear relationship; Preferably, y1 and x satisfy the following relationship: y1 = a1x 2 +b1x+c1, where a1 is 6.55-6.65, b1 is 6.45-6.55, and c1 is -7.0~-2.
5.
3. The composite positive electrode sheet according to claim 1, characterized in that: The first main material layer further includes a first conductive agent, the second main material layer further includes a second conductive agent, the sum of the mass fractions of the first conductive agent and the second conductive agent / (the sum of the mass fractions of the layered oxide material and the polyanion positive electrode material)×100 is y2, the thickness ratio of the first main material layer and the second main material layer is z, and y2 and z satisfy a binary linear relationship; Preferably, y2 and z satisfy the following relationship: y2=a2z 2 -b2z+c2, where a2 is 2.2-2.4, b2 is 2.5-3, and c2 is 5-6; Preferably, the thickness ratio of the first main material layer to the second main material layer is (3-5):(6-8).
4. The positive electrode sheet according to claim 2 or 3, characterized in that: The first conductive agent comprises any one of graphite, multi-walled carbon nanotubes, graphene, SP or acetylene black or a combination of at least two thereof, preferably multi-walled carbon nanotubes; Preferably, the second conductive agent includes any one of graphite, multi-walled carbon nanotubes, graphene, SP or acetylene black or a combination of at least two thereof, preferably any one of graphite, graphene, SP or acetylene black or a combination of at least two thereof.
5. The positive electrode sheet according to any one of claims 1 to 3, characterized in that: The first main material layer also includes a first adhesive; Preferably, in the first main material layer, the mass ratio of the layered oxide material, the first conductive agent and the first binder is (25-40):(0.8-1.6):(0.3-1.2).
6. The positive electrode sheet according to any one of claims 1 to 3, characterized in that: The second main material layer also includes a second adhesive; Preferably, in the second main material layer, the mass ratio of the polyanion positive electrode material, the second conductive agent and the second binder is (59-78):(3-4):(1.2-1.6).
7. The positive electrode sheet according to any one of claims 1 to 3, characterized in that: The layered oxide material includes any one of sodium nickel cobalt manganate, sodium metaferrite or sodium nickel cobalt aluminum oxide, or a combination of at least two thereof. Preferably, the polyanion positive electrode material includes sodium vanadium phosphate and / or sodium vanadium fluorophosphate.
8. A method for preparing a positive electrode sheet according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: (1) coating a first main material layer slurry on at least one side surface of a current collector, and after drying, obtaining a first main material layer on at least one side surface of the current collector; (2) coating the second main material layer slurry on the surface of the first main material layer in step (1), and after drying, obtaining a positive electrode main material layer on at least one side of the current collector to obtain the positive electrode sheet; The first main material layer slurry includes a layered oxide material, and the second main material layer slurry includes a polyanion positive electrode material; The mass ratio of the layered oxide material to the polyanion positive electrode material is (1-3):(3.1-5).
9. A battery, characterized in that: The battery comprises the positive electrode sheet as described in any one of claims 1 to 7, or the positive electrode sheet prepared by the preparation method as described in claim 8.
10. An electrical device, characterized in that: The electric device comprises the battery as claimed in claim 9.
